THE USE OF GIST STRATEGY IN READING COMPREHENSION - Agnes Budi Tyas Mekawati; Ch. Evy Tri W (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
The objectives of the research are as follows : (1) To know whether using GIST strategy can improve the reading comprehension at the eighth grade students of SMP Saverius Sragen in the Academic Year of 2019/2020. (2) To know how far the implementation of GIST strategy in teaching and learning reading in narrative text at the eighth grade students of SMP Saverius Sragen in Academic Year 2019/2020. The researcher conducted a Classroom Action Research at the eighth grade students of SMP Saverius Sragen from January to February 2020. The subject of the research was the students of VIII A which consisted of 20 students. The research was concerned on improving students‟ reading comprehension using GIST strategy. It consisted of 2 cycles. Each cycle consisted of two meetings which was 80 minutes for each meeting and every cycle ended by post test. Each cycle had four steps: planning, action, observation and reflection. In collecting the data, the researcher used observation, interview, documentation, and tests(pre-test and post-test). The result of cycle 1 showed that some students had lack of vocabulary and also still had difficulties in finding the main idea, the implicit information and the meaning of difficult words in a text. Therefore, cycle 2 showed that the use of GIST strategy for students had lack of vocabulary and difficulties in finding the main idea could improve the students‟ reading comprehension. The students‟ mean score in pre-test was 50.25, post-test I was 66.75, and post-test II 76.80. Based on the result of the research, it could be concluded that “The use GIST (Generating Interaction between Schema and Text) strategy can improve students‟ reading comprehension in narrative text at the eighth grade students of SMP Saverius Sragen in 2019/2020 academic year especially in class VIII-A”. Key word: Reading Comprehension, GIST Strategy, Classroom Action Research.